The Effects of School Principals' Leadership Style, Work Motivation, and Work Discipline on Teacher Pedagogical Competencies - Rini Mutia; Niswanto Niswanto; Yusrizal Yusrizal (STAI Hubbulwathan Duri, 2021)
This study aimed to elicit data regarding the effect of school administrators' leadership styles, work motivation, and work discipline on teacher pedagogical competency. This study employs a quantitative methodology. The researchers conducted a quantitative study to demonstrate the effect of the principal's leadership style, work motivation, and work discipline on the pedagogical competency of teachers at SMA Negeri 1 Badar, Aceh Tenggara Regency. The findings indicate that principal leadership has a considerable effect on teacher performance and that teacher work motivation greatly affects teacher performance. Principal leadership and teacher work motivation have a major impact on teacher performance. The purpose of this study was to elicit data regarding the effect of school administrators' leadership styles, work motivation, and work discipline on teacher pedagogic competency. This study employs a quantitative methodology. The researchers conducted a quantitative study to demonstrate the effect of the principal's leadership style, work motivation, and work discipline on the pedagogical competency of teachers at SMA Negeri 1 Badar, Aceh Tenggara Regency. The findings indicated that principal leadership has a substantial effect on teacher performance, that teacher work motivation has a significant effect on teacher performance, and that principal leadership and teacher work motivation significantly affect teacher performance.